Sample introduction interface for on-chip nucleic acid-based analysis of Helicobacter pylori from stool samples. Issue 11 (10th May 2016) - Mosley, O.; Melling, L.; Tarn, M. D.; Kemp, C.; Esfahani, M. M. N.; Pamme, N.; Shaw, K. J.
Abstract : Processing of stool samples using an IFAST microfluidic device for the genetic analysis of infectious pathogens such as H. pylori . Abstract : Despite recent advances in microfluidic-based integrated diagnostic systems, the sample introduction interface, especially with regards to large volume samples, has often been neglected. We present a sample introduction interface that allows direct on-chip processing of crude stool samples for the detection of Helicobacter pylori ( H. pylori ). The principle of IFAST (immiscible filtration assisted by surface tension) was adapted to include a large volume sample chamber with a septum-based interface for stool sample introduction. Solid chaotropic salt and dry superparamagnetic particles (PMPs) could be stored on-chip and reconstituted upon sample addition, simplifying the process of release of DNA from H. pylori cells and its binding to the PMPs. Finally, the PMPs were pulled via a magnet through a washing chamber containing an immiscible oil solution and into an elution chamber where the DNA was released into aqueous media for subsequent analysis. The entire process required only 7 min while enabling a 40-fold reduction in working volume from crude biological samples. The combination of a real-world interface and rapid DNA extraction offers the potential for the methodology to be used in point-of-care (POC) devices.